Experimental study on the temperature of the contact strip in sliding electric contact. (October 2017) - Chen, GX; Hu, Y; Dong, BJ; Yang, HJ; Gao, GQ; Wu, GN; Zhang, WH; Zhou, ZR
Using a ring-on-block tester with AC, the authors accomplished several experimental tests on the temperature of the contact wire and strip in sliding electric contact. In the test, the temperature of the samples, arc voltage, electric current, and wear volume of the strip were collected. Influences of the normal force, sliding speed, and electric current on the temperature of the contact wire and strip were studied. Test results show that the temperature of the carbon strip increases with the increasing of sliding speed and electric current or the decreasing of normal force. The strip wear rate is linearly related with the temperature of the strip. Moreover, the factors affecting the strip temperature were also discussed.